Perspective of adolescent homosexual sons and their mothers on the changes on parent-child relations after disclosure - Alip, Alex Bienvenido L. III; Teves, Maria Beatrice P.
ABSTRACT The study aimed to determine and understand the relationship of adolescent homosexual sons and their parents before and after the disclosure of sexual identity in the perspective of adolescent homosexual sons and their mothers. It looked into the perceived changes which disclosure brings to the interaction between adolescent homosexual sons and their parents. In line with this, the study observed how parental views on homosexuality affect their responses to the disclosure of adolescent homosexual sons. In addition, both sons? and parents? methods of dealing with the situation brought about by disclosure were reported. The study used qualitative data gathering that involves interviews of 15 disclosed-adolescent homosexual male college students and 14 of their mothers. Mothers and sons were interviewed separately following a series of questions. These interviews were tape-recorded and the data transcribed was thematically analyzed. Results showed that adolescent homosexual sons perceive changes in parent-child relationship in terms interaction, communication, and discipline. Similarly, their mothers report such changes with an addition of being more protective of their sons after the event of disclosure. Furthermore, both perspectives discuss the ways in which the adolescent homosexual sons and their mothers deal with situation brought about by disclosure setting different rules and conditions. It is vital for homosexual individuals and their parents to look into these changes and methods of dealing with disclosure to help both parties achieve positive attitudes on homosexuality and promote healthy relationships. In addition, society should be more sensitive and aware of these concerns regarding homosexuality.